Effect of mcconnell taping on pain, rom & grip strength in patients with triangular fibrocartilage complex injury - Mohd Dar, Shahid; Arunmozhi, R; Sharma, Babloo (Scientific Research Journal of India, 2013)
STUDY OBJECTIVES: To find out the efficacy of McConnell Taping on Pain, Range of Motion and Grip strength in subjects with Triangular Fibrocartilage Complex (TFCC) injury. DESIGN: An Experimental Study. SETTING: All the Subjects were selected from various sports center from Dehradun and SAI Guwahati. Methods: A total of 28 subjects were recruited for the study on the basis of inclusion and exclusion criteria after signing the informed consent form. The subjects were divided into two Groups (A= Taping & B= Conventional Therapy). OUTCOME MEASURE: Grip Strength, Range of Motion for Wrist and Forearm & Numerical Pain Rating Scale. RESULTS: The result of the study shows that both McConnell Taping and Conventional Therapy are effective in improving the Range of Motion, Grip Strength and reducing the Pain level. Both groups showed significant improvement when comparison was made within the group. However, there is significant reduction in pain level between the groups for Group A (p=0.000). CONCLUSION: The present study demonstrates that both McConnell Taping and Conventional Treatment are effective in improving the Grip Strength, Range of Motion and reducing the Pain level in subjects with TFCC injury. However, it can be concluded that McConnell Taping is the better form of treatment in improving the Grip Strength, Range of Motion and reducing the Pain level in subjects with TFCC injury.